Log in to add a comment

## Answers

The Brainliest Answer!

### This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.

__we eliminate the xy term.__8 y - 3 x = 5 x y --- equation (1)

6 y - 5 x = - 2 x y ---- equation (2)

multiply (1) by 2 and multiply (2) with 5 and then add,

16 y - 6 x + 30 y - 25 x = 10 x y - 10 x y

46 y - 31 x = 0

so y = 31/46 * x --- (3)

substitute this value of y in (1).

8 * 31/46 x - 3 x = 5 x * (31/46 x)

multiply by 46 and divide by x :

248 - 138 = 155 x

x = 110 / 155 = 22/31

y = 31/46 * 22/31 = 11/23

=========================

__another way:__Divide equations (1) and (2) by xy:

8 / x - 3 / y = 5 and 6 / x - 5 / y = - 2

call 1/x = X and 1/y = Y

8 X - 3 Y = 5 --- (3)

6 X - 5 Y = -2 --- (4)

*we eliminate X by (3) * 3 - (4) * 4*24 X - 9 Y - 24 X + 20 Y = 15 + 8

11 Y = 23

=> Y = 23 /11

**=> y = 11/23**substitute this in (3)

8 X - 3 * 23 /11 = 5

8 X = 5 + 69/11 = 124/11

X = 31/22

*=> x = 22/31*